POLYCYSTIC OVARIAN SYNDROME - T. D. Guriev (IRBIS LLC, 2016)
Polycystic ovarian syndrome (PCOS) is a rather common disease which represents one of the most topical issues of gynecological endocrinology. This review article presents modern data on etiology and pathogenesis of PCOS and provides substantiation for frequent combination of hyperandrogenia and insulin resistance during PCOS. Also, considerations are given to the characteristic clinical manifestations of PCOS and modern approaches to its diagnosis and treatment. The latter includes drugs which affect the neuromediator systems (sibutramine, orlistat), drugs of the insulin sensitizing group (metformin, progestagens or low dose, single phase, third generation oral contraceptives (COC) combined with progestagens), synthetic anti estrogens (clostilbegit) and other medications. The outlook and methods of surgical intervention, as well as treatment tactics during infertility at the backdrop of PCOS, are addressed.